Economic Performance of Ginger (Zingiber officinale Rose.) Cultivation in Some Selected Locations of Bangladesh (Bangladesh Journal of Agricultural Research, 2012)
The study was conducted in two ginger growing districts, namely Nilphamari  and Khagrachari of Bangladesh during the period of 2009-10 to estimate the technical efficiency of ginger growers. The study revealed that ginger production was profitable and the average benefit cost ratio (BCR) was found 2.17. The estimated results showed that the average level of technical efficiency among the sample farmers was 85. This implies that given the existing technology and level of inputs, the output could be increased by 15 percent. In inefficiency model, the coefficient of farmers education and experience in ginger cultivation was negative and significant. Sixty eight percent farmers produced outputs to the maximum frontier output level (81-95%). Farmers in the study area also mentioned some problems like incidence of root rot disease, high price of seed, insect infestation etc to its production. DOI: http://dx.doi.org/10.3329/bjar.v37i1.11182 Bangladesh J. Agril. Res. 37(1): 109-120, March 2012